Application of Good Farming Practices for Laying Hens in Suruhwadang Village, Blitar District - Riyanto, Riyanto; Kristanti, Novita Dewi; Almawachida, Amelia Rista (Faculty of Animal Science, Universitas Brawijaya, 2025)
The daily egg production (hen-day production) of layer-phase laying hens aged 72 weeks in Suruhwadang Village is below the standard, recorded at approximately 65–70%, whereas the ideal standard is approximately 79–81%. This discrepancy highlights the need to encourage farmers to optimize egg production through the implementation of good farming practices (GFPs), as outlined by the Indonesian Minister of Agriculture Regulation No. 31 of 2014. This study aimed to evaluate the application of GFP and its effect on the daily egg production of laying hens in Suruhwadang village. This study was conducted from December 2022 to May 2023 in Kademangan District, Blitar Regency, and involved 30 layers breeders selected via purposive sampling. The study employed a quantitative research approach with a survey method, and the data were analysed via descriptive and inferential statistical techniques, including multiple linear regression analysis. The findings revealed that the application of Good Farming Practices in Suruhwadang Village is generally poor. However, it was determined that the GFP significantly influences daily egg production, contributing 41.1% of the variance in egg production, with a significance value of 0.019. These results underscore the importance of enhancing GFP adoption to improve egg production and meet industry standards.